PENGARUH SELF-EFFICACY TERHADAP PRESTASI BELAJAR BAHASA ARAB PESERTA DIDIK DI MTS AL-IKHWAN BAUBAU - Najam Ahmad, Fitratun; Usman, Syahruddin; Kasim, Amrah (Inspiratif Pendidikan, 2022)
This study aims to describe the self-efficacy and learning achievement of Arabic students at Mts Al-Ikhwan Baubau, as well as to examine the effect of self-efficacy on Arabic learning achievement of students at Mts Al-Ikhwan Baubau. This research uses quantitative method with causal associative type. The population of this study were all students at Mts Al-ikhwan Baubau who were in class VIII and IX as many as 46 students, the sample in this study were all members of the population. Data collection techniques were carried out using questionnaires and tests. The collected data were analyzed using descriptive analysis and inferential analysis. The results obtained: 1) self-efficacy and Arabic learning achievement of students at Mts Al-Ikhwan Baubau are in the medium category. 2) the results of inferential statistical calculations obtained p-value <α (0.008 <0.05) and the regression coefficient (b) of 0.224 so that H0 is rejected and H1 is accepted, this means that self-efficacy has a positive effect on participants' Arabic learning achievement educate.